Age at menarche in schoolgirls with and without excess weight - Silvia D. Castilho; Luciana B. Nucci (Elsevier, 2015)
Objective: To evaluate the age at menarche of girls, with or without weight excess, attending private and public schools in a city in Southeastern Brazil. Methods: This was a cross-sectional study comparing the age at menarche of 750 girls from private schools with 921 students from public schools, aged between 7 and 18 years. The menarche was reported by the status quo method and age at menarche was estimated by logarithmic transformation. The girls were grouped according to body mass index (BMI) cut-off points: (thin + normal) and (overweight + obesity). In order to ensure that they belonged to different strata, 328 parents of these schools answered a questionnaire to rate the student's socioeconomic level. Results: Menarche was reported by 883 girls. Although they belonged to different classes (p < 0.001), there was no difference in the nutritional diagnosis (p = 0.104) between them. There was also no difference in age at menarche between the girls studying in private (12.1 years, 95% CI: 12.0-12.2) and public schools (12.2 years, 95% CI:12.1-12.3; p = 0.383). When evaluated by nutritional status, there was difference only in the age at menarche between girls from private schools with excess weight and without excess weight (11.6 and 12.3 years; p < 0.001). The girls with excess weight attending private schools also had earlier an menarche than those attending public schools (respectively, 11.6 and 12.1 years; p = 0.016). Conclusions: Although the students from private schools belonged to a higher socioeconomic status, there is currently no longer a large gap between them and girls from public schools regarding nutritional and socioeconomic factors that may influence the age at menarche. Resumo: Objetivo: Avaliar a idade da menarca em meninas, com e sem excesso de peso, que frequentam escolas particulares e públicas de uma cidade do sudeste do Brasil. Métodos: Estudo transversal que comparou a idade da menarca de 750 meninas de escolas particulares com 921 alunas de escolas públicas, com idades entre sete e 18 anos. A menarca foi relatada pelo método status quo e a idade da mesma estimada pelo logito. As meninas foram agrupadas pelos pontos de corte do IMC em (magreza + eutrofia) e (sobrepeso + obesidade). Com o intuito de certificar que elas pertenciam a classes diferentes, 328 pais responderam a um questionário para classificar o nível econômico dos alunos. Resultados: A menarca foi referida por 883 meninas. Embora elas pertençam a classes econômicas distintas (p < 0,001), não houve diferença quanto ao diagnóstico nutricional (p = 0,104). Também não houve diferença na idade da menarca entre as que estudam em escolas particulares (12,1 anos; IC95%%: 12,0-12,2) e públicas (12,2 anos; IC95%%: 12,1-12,3); p = 0,383. Quando avaliadas pelo diagnóstico nutricional só houve diferença na idade da menarca das meninas com e sem excesso de peso de escolas particulares (11,6 e 12,3 anos; p < 0,001). As meninas com excesso de peso das escolas particulares também menstruaram mais cedo do que as das escolas públicas (respectivamente, 11,6 e 12,1 anos; p = 0,016). Conclusões: Embora as alunas das escolas particulares ainda pertençam a classes mais altas, atualmente, não existe mais um abismo nutricional e socioeconômico tão grande entre elas quanto a fatores que podem influenciar na idade da menarca. Keywords: Menarche, Adolescent, Body mass index, Palavras-chave: Menarca, Adolescente, Índice de massa corporal